URGENSI PENERAPAN CALESTIAL MANAGEMENT BAGI PENINGKATAN KUALITAS SDM PADA IKNB SYARIAH - Trimulato, Trimulato (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
The non-bank syariah financial industry (IKNB Syariah) in Indonesia continues to experience a very good improvement. The growth of IKNB Syariah is seen in the total assets of IKNB syariah in 2010, 9,333 billion rupiah, in year rose to 46,895 billion rupiah. With an average growth rate of 62.29%. Therefore, the development of IKNB syariah must be balanced with sufficient resources and quality. OJK efforts have been made in improving the quality of human resources in IKNB Syariah with two big strategies. This research uses a qualitative descriptive type, Limitation in this paper is focused on OJK efforts in improving the existing human resources IKNB syari'ah. The need for application of celestial management for human resources in IKNB syariah. The results of this paper that OJK has set two strategies in an effort to improve the quality of human resources in IKNB sharia. Then the need for application of celestial management for human resources in IKNB sharia to create good quality. Because IKNB sharia is a business institution that can not be separated from religious or spiritual aspect. So it requires the right concept in improving the quality of human resources it has.